CHALLENGES OF USING: IN UKRAINE OR ON UKRAINE - Magryts’ka, I. V.; Homa, R. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The word form on Ukraine, non-normative for the modern Ukrainian literary language, is used by the undereducated Ukrainians, accustomed to the former more stable form, or by pro-Russian mass media in Ukraine, or by Russians – from ordinary citizens to highly educated philologists and highrank politicians. However, this form contradicts the norms of the modern Russian literary language. It has a vivid political context and proves the principal unwillingness of Russians to recognize the independence of the Ukrainian state, highlights their imperial ambitions in regard to Ukraine. The authors recommend Russian philologists to remain philologists and use the expression in Ukraine when talking about the country that has been recognized by the world community.